The Influence of Store Atmosphere and Experiential Marketing on Customer Satisfaction and Its Impact on Word of Mouth : Study on Jay Coffee Consumers - Dela Nur Hikmah (International Journal of Economics and Management Sciences, 2025)
The coffee shop industry in Samarinda City is growing rapidly driven by the hangout culture and increasing coffee consumption. Jay's Coffee, as one of the well-known coffee shops, faces challenges in maintaining customer satisfaction and increasing word of mouth amidst competition. This study analyzes the effect of store atmosphere and experiential marketing on customer satisfaction and its impact on word of mouth. Using a quantitative method with a survey, this study involved 97 Jay Coffee customers selected by non-probability sampling. Data were collected through questionnaires and analyzed with path analysis. The results showed that store atmosphere and experiential marketing have a positive and significant effect on customer satisfaction. A comfortable store atmosphere and interesting experiences increase customer satisfaction, which in turn encourages word of mouth. In addition, store atmosphere and experiential marketing also have a direct effect on word of mouth. Thus, Kopi Jay needs to develop strategies to improve store atmosphere and customer experience to maintain loyalty and improve business competitiveness.